Relevansi Pemikiran Ekonomi Abu Yusuf dan Al Syaibani dengan Kebijakan Ekonomi di Indonesia - Mubarok, Anas Bayan; Witro, Doli (TAWAZUN: Journal of Sharia Economic Law, 2022)
Abu Yusuf and Al-Syaibani are great Islamic economists who gave birth to basic principles ini the economy. Through their thinking, they succeeded in bringing governments in their time to peak prosperity in economic development. This study aims to explain the economics of Abu Yusuf and Al-Syaibani's thinking and its relevance in Indonesian economic policies. This research belongs to the type of qualitative research, and the method of collecting data is library research. Research shows that: first, Abu Yusuf’s economic thinking can be found in his work al-kharaj, the core of his economic thinking speaks of the emphasis on the responsibility of rulers to welfare their people. Second, Al-Syaibani, in his economic view, is more likely to talk about micro-economic issues. Third, the economic thinking of these two figures has relevance to the economic policies implemented in Indonesia.